Pengaruh Media Sosial Word Of Mouth Terhadap Keputusan Pembelian Konsumen Online Fast Fashion - Zed, Etty Zuliawati; Bilqis, Mutiara Zahra; Purnama, Mega lenita; Wulandari, Ririn; Aladawiyah, Robiah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study sets out to examine the influence of social media and word of mouth (WOM) on purchasing decisions for fashion products among young consumers. In the digital era, social media has become the main platform for interacting and sharing information about products, which can influence consumer behavior. Based on a literature review, this study identified various factors that influence purchase decisions, such as influencer marketing, electronic word of mouth (eWOM) and brand awareness. The results say social media and WOM have a significant effect on purchasing decisions. Effective communication through social media is proven to increase consumer motivation to buy products. This study concludes that marketing strategies using social media and WOM can increase the attractiveness of fashion products in a competitive market. The findings provide important guidance for marketers in designing more effective campaigns to increase sales through the power of social media.